Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.2218/ijdc.v7i2.233
|View full text |Cite
|
Sign up to set email alerts
|

The Data Management Skills Support Initiative: Synthesising Postgraduate Training in Research Data Management

Abstract: This paper will describe the efforts and findings of the JISC Data Management Skills Support Initiative (‘DaMSSI’). DaMSSI was co-funded by the JISC Managing Research Data programme and the Research Information Network (RIN), in partnership with the Digital Curation Centre, to review, synthesise and augment the training offerings of the JISC Research Data Management Training Materials (‘RDMTrain’) projects.DaMSSI tested the effectiveness of the Society of College, National and University Libraries’ Seven Pilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…Halbert in Gunjal and Gaitanou (2017, p. 10), too, observed a lack of a sense of priority amongst researchers. Additionally, issues relating to culture are also evident in previous studies (Anduvare, 2019;Avuglah, 2016;Molloy and Snow, 2012;Morgan et al, 2017;Pinfield et al, 2014;Cox et al, 2017). Anduvare's (2019) study, for example, revealed that most universities face a cultural challenge when adopting RDM, in the sense that not every stakeholder will find it easy to migrate from one form of managing and handling data to another.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…Halbert in Gunjal and Gaitanou (2017, p. 10), too, observed a lack of a sense of priority amongst researchers. Additionally, issues relating to culture are also evident in previous studies (Anduvare, 2019;Avuglah, 2016;Molloy and Snow, 2012;Morgan et al, 2017;Pinfield et al, 2014;Cox et al, 2017). Anduvare's (2019) study, for example, revealed that most universities face a cultural challenge when adopting RDM, in the sense that not every stakeholder will find it easy to migrate from one form of managing and handling data to another.…”
Section: Resultsmentioning
confidence: 65%
“…Numerous scholars and studies identify several competencies for better provision of RDM services in universities. Despite several identified RDM competencies and skills, most scholars agree that data curation skills are the most important for RDM services and practices (Molloy and Snow, 2012;Tripathi et al, 2017;Woeber, 2017;Nhendodzashe and Pasipamire, 2017;Chiware and Becker, 2018;Cox et al, 2019;Masinde et al, 2021). Data skills, sustained awareness of data creation, organisation, validation, sharing and curation are also identified as necessary RDM skills and knowledge (Molloy and Snow, 2012, p. 251).…”
Section: Purposementioning
confidence: 99%
See 2 more Smart Citations
“…DMPs represent the basic level of both RDM and RDS. Preparing DMPs has been the first and widespread activity that complies with the varied requirements of funding agencies (Molloy and Snow, 2012). There is also a model for assessing requirements for RDM support (Lyon et al, 2014), and -in general -it can be said that RDS has become a new embedded information service (Si et al, 2013).…”
Section: Research Data Servicesmentioning
confidence: 99%